Influence Covid-19 Disinformation Against Panic- Buying Attitudes in Family Whatsapp Groups - Wibawa, Damar Agung Khrisna; Sembada, Windhiadi Yoga; Mardani, Puri Bestari (KOMUNIKA, 2022)
This study aims to determine how much influence the distribution of disinformation in the family whatsapp group has on the panic buying attitude of middle-aged housewives in South Jakarta. With the rise of panic buying actions that occurred during the period leading up to the strict PSBB period in April 2020, researchers wanted to see if there was an influence on the use of social media, especially WhatsApp, which had increased since this pandemic happened. The method used in this research is quantitative with explanatory type. Information Integration Theory from Martin Fishbein is the theory chosen by the researcher in this research. The sample in this study amounted to 204 middle-aged housewives living in South Jakarta, which were divided based on the proportion per district using a purposive sampling technique. The results of this study found a very strong relationship and influence between the distribution of disinformation in the family whatsapp group and the panic buying attitude of middle-aged housewives in South Jakarta. The dimensions of the theory used by researchers, namely the valence and weight of information on disinformation messages were found to have a strong relationship and influence with the panic buying attitude of middle-aged housewives in South Jakarta. The government and the public often pay more attention to the spread of disinformation messages to prevent emotional contagion that leads to panic buying in South Jakarta. The dimensions of the theory used by researchers, namely the valence and weight of information on disinformation messages were found to have a strong relationship and influence with the panic buying attitude of middle-aged housewives in South Jakarta. The government and the public often pay more attention to the spread of disinformation messages to prevent emotional contagion that leads to panic buying in South Jakarta. The dimensions of the theory used by researchers, namely the valence and weight of information on disinformation messages were found to have a strong relationship and influence with the panic buying attitude of middle-aged housewives in South Jakarta. The government and the public often pay more attention to the spread of disinformation messages to prevent emotional contagion that leads to panic buying in South Jakarta.